Using stable isotopes as tracers of water masses and nutrient cycling processes in the Gulf of Maine. (13th December 2020) - Whitney, Nina M.; Wanamaker, Alan D.; Switzer, Megan E.; Pettigrew, Neal R.
Abstract: The dramatic marine environmental change seen today can be difficult to fully document and interpret without adequate, spatially and temporally comprehensive, baseline datasets of hydrographic properties. Here we present isotope data measured in water samples collected during a nine-day research cruise in October 2016 throughout the Gulf of Maine, a rapidly changing region of the world's oceans. A comparison of the oxygen isotopes of the water (δ 18 Owater ) and salinity data reveal that water samples fall on a tight, linear mixing line between fresher shelf water and saltier slope waters, with the freshwater endmember originating from much higher latitudes (the Gulf of St. Lawrence and the Labrador Sea). Some subtle differences in freshwater endmembers are observed between the three different deep basins in the Gulf of Maine. These differences are likely reflecting differences in freshwater input and vertical mixing between the different basins. Additionally, these water samples have lower δ 18 Owater values for a given salinity value than previously published values of marine water mass endmembers. This offset may be related to systematic changesin water mass endmember values or year to year variability, as well as differences in the proportions of water masses entering the Gulf of Maine. Nitrogen and oxygen isotopes of dissolved nitrate (NO3 − ; δ 15 NNO3- and δ 18 ONO3-, respectively) measured in the water samples suggest a strong influence of phytoplankton assimilation near the surface in both isotopic systems. Combining these two datasets using Δ(15, 18) to look at the rates of fractionation between the two isotope systems reveals potential water column nitrification above 100 m in most places in the Gulf of Maine. This finding provides support for previous hypotheses of water column nitrification in the Gulf of Maine based on nutrient distribution and nitrogen box modeling. However, these calculations rely on the assumption that all nitrate is sourced from deeper waters. It is possible these results are instead caused by NO3 − from different sources at the surface and therefore do not necessarily indicate the presence of nitrification. Highlights: Differences in d 18 Owater in different Gulf of Maine basins suggest differences in vertical mixing and freshwater input. d 15 NNO3- and d 18 ONO3- values of Gulf of Maine water samples suggest significant influence of phytoplankton assimilation. The Δ(15, 18) variable suggests nitrification is occurring in the upper water column throughout much of the Gulf of Maine.